2014
DOI: 10.1159/000360862
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Comparison on the Risk of Haemorrhage with Different Sizes of Biopsy Needles for Stereotactic Brain Biopsy

Abstract: Aim: To compare the risk of postoperative haemorrhage with different sizes of brain biopsy needles. Patients and Method: A cohort of patients using a 2.5-mm outer diameter side-cutting biopsy needle was compared to a subsequent cohort using a 1.8-mm needle of the same type. All data were collected prospectively. A CT scan was done within 12 h after surgery. Any visible haemorrhage at the operated site was documented. Results: From 2007 to 2013, 54 stereotactic brain biopsies (all frameless except for one frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
0
15
1
Order By: Relevance
“…Only speculations are possible as to why this has occurred, statistical evidence not pointing to any reason in particular. Some reports [ 18 ] suggest that the size of the needle correlates with the risk of hemorrhage, but this could not be established in our series (outer needle diameter 2.2 and 1.8 mm and cutting window length 7 and 10 mm for the Stealth Treon TM Vertek® and Brainlab® Varioguide, respectively).…”
Section: Discussioncontrasting
confidence: 59%
“…Only speculations are possible as to why this has occurred, statistical evidence not pointing to any reason in particular. Some reports [ 18 ] suggest that the size of the needle correlates with the risk of hemorrhage, but this could not be established in our series (outer needle diameter 2.2 and 1.8 mm and cutting window length 7 and 10 mm for the Stealth Treon TM Vertek® and Brainlab® Varioguide, respectively).…”
Section: Discussioncontrasting
confidence: 59%
“…STB[ 2 3 4 5 13 15 18 19 20 21 22 23 24 ] has been demonstrated to be a low-risk procedure and may be performed with extreme accuracy (1 mm variance), especially with use of recent system compatible with CT scan and/or MRI. On the other hand, ultrasound-guided biopsy is also safe, cheap, quick, simple to perform, and technically reliable real-time method for superficially located lesions as well as for deep-seated lesions, independent of size.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, a brain tumor biopsy not only is costly 7 but also poses risks inherent to an invasive procedure. 8,9 An imaging based characterization also presents other advantages, 10 such as permitting interrogation of tumor heterogeneity characteristics and an assessment of tumor pathophysiology. More recently, it has also been suggested that GBMs harbor multiple cell subpopulations; 11 hence, an imaging based examination can also provide an insight into the molecular programs driving the disease.…”
Section: Introductionmentioning
confidence: 99%